Decline in Liver Mitochondria Metabolic Function Is Restored by Hochuekkito Through Sirtuin 1 in Aged Mice With Malnutrition - Nahata, Miwa; Fujitsuka, Naoki; Sekine, Hitomi; Shimobori, Chika; Ohbuchi, Katsuya; Iizuka, Seiichi; Mogami, Sachiko; Ohnishi, Shunsuke; Takeda, Hiroshi (Frontiers in Physiology, 2022)
Malnutrition impairs basic daily activities and leads to physical frailty, which is aggravated in the elderly compared with young adults. It is also well known that the elderly are more vulnerable to metabolic stress. Therefore, in this study, using a food restricted (FR) mouse, we aimed to evaluate the effect of aging on locomotor activity and liver metabolic function. Further, we also investigated the involvement of hepatic mitochondria in liver metabolic function during aging, as well as the therapeutic benefit of the traditional Japanese medicine, hochuekkito (HET). Our findings indicated that following food restriction provided as 30% of ad libitum intake for 5 days, the locomotor activity was lower in 23–26-month-old (aged) mice than in 9-week-old (young) mice. Further, compared with young mice, aged mice exhibited significant decreases in the levels of metabolites related to the urea cycle, mitochondrial function, and anti-oxidative stress. The livers of the aged mice also showed a greater decrease in mitochondrial DNA copy number than young mice. Furthermore, the gene expression levels of sirtuin 1 (SIRT1) and mitochondrial biogenesis-related regulators were attenuated in aged mice. However, these changes were partially restored by HET treatment, which also improved locomotor activity, and combined treatment with alanine resulted in more significant effects in this regard. Therefore, our findings suggested that the decrease in locomotor activity in aged FR mice was associated with a decline in the metabolic function of hepatic mitochondria via decreased SIRT1 expression, which was restored by HET treatment. This implies that enhancing the metabolic function of liver mitochondria can contribute to alleviating energy deficiency in the elderly.